Mode II fracture of wood: Comparison between End-Notched Flexure and Compact Shear testing. (July 2022) - Reiner, Johannes; Wood, Jake; Subhani, Mahbube
Abstract: End-Notched Flexure (ENF) and Compact Shear (CS) tests were performed on Australian Radiata Pine to quantify Mode II fracture properties in wood. Capabilities and limitations of each fracture test are compared with respect to ease of testing, underlying reduction schemes to determine Mode II fracture toughness (or strain-energy release rate), stable crack growth and mixed mode behaviour during crack growth. In particular, different reduction schemes are presented with and without the need for cumbersome crack length measurements. In contrast to CS tests, it is found that ENF tests yield stable and reliable Mode II fracture with negligible mixed-mode behaviour. Considering resistance curves, crack length measurements are only needed to determine initial fracture energy values associated with crack length values up to 20 mm while compliance-based beam theory can be used to calculate steady-state fracture energies by means of an equivalent crack length that only requires global load–displacement test data. Highlights: Direct comparison of End-Notched Flexure (ENF) and Compact Shear (CS) tests. Both tests result in similar energy release rate values in the RL and TL planes ranging from 1.34 N/mm up to 1.49 N/mm. ENF tests yield stable and reliable Mode II fracture with negligible mixed-mode behaviour. CS tests include unwanted Mode I contributions of up to 35%.